Clinical Characteristics of Patients With Chronic Stevens-Johnson Syndrome Treated at a Major Tertiary Eye Hospital Within the United Kingdom - Jabbour, Samir; Din, Nizar; Logeswaran, Abison; Taberno Sanchez, Sara; Ahmad, Sajjad (Frontiers in Medicine, 2021)
This is a retrospective case note review of 91 patients with chronic Stevens Johnson syndrome (SJS) treated at Moorfields Eye Hospital (London, United Kingdom). This was done to determine the clinical needs and outcomes of patients in order inform future care pathways. Approximately a half of patients were White British but there were significant numbers of patients from other ethnic groups, South Asian and Black in particular. Oral antibiotics were the causative agent in almost a half of the patients with SJS, systemic infections in 14%, non-steroidal anti-inflammatory drugs in 8% and anticonvulsants in 7%. The age of onset was varied but a significant proportion of patients developed acute SJS in childhood. One patient had suffered from SJS for over 70 years. There was a significant correlation between visual acuity at initial referral to final recorded vision. It was also noted that vision continued to significantly deteriorate over time despite therapeutic interventions. Our regression model shows that approximately 62% of the variance in final vision can be explained by the initial vision, duration disease and the presence of corneal keratin and limbal stem cell deficiency. The majority of our patients were on advanced ocular surface treatments including serum drops, topical ciclosporin and retinoic acid drops. Of particular significance, approximately a third of our patient cohort was also on systemic immune suppression.